2021
DOI: 10.3389/fphys.2021.687121
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Hypofunction in the Aging-Associated Malfunction of Peripheral Tissue

Abstract: Glutamatergic transmission through NMDA receptors (NMDARs) is important for the function of peripheral tissues. In the bone, NMDARs and its co-agonist, D-serine participate in all the phases of the remodeling. In the vasculature, NMDARs exerts a tonic vasodilation decreasing blood perfusion in the corpus cavernosum and the filtration rate in the renal glomerulus. NMDARs are relevant for the skin turnover regulating the proliferation and differentiation of keratinocytes and the formation of the cornified envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…We found that D-serine supplementation decreases the number of perseverative errors in a reversal learning task in middle-aged and aged rats by increasing the functional connectivity between frontal association areas with retrosplenial and cingulate cortex. Furthermore, D-serine supplementation did not induce nephrotoxicity; instead, it restored the thickness of the epithelial tissue in the straight portion of proximal renal tubules of senescent rats suggesting that D-serine can reverse the detriment of aging-associated malfunction of peripheral tissue ( Rivera-Villaseñor et al, 2021 ). D-serine did not improve cognitive flexibility in young rats showing that D-serine effect is age-dependent pointing to a possible intervention in restoring the levels of D-serine to reverse cognitive functions that are affected in the aged brain.…”
Section: Discussionmentioning
confidence: 99%
“…We found that D-serine supplementation decreases the number of perseverative errors in a reversal learning task in middle-aged and aged rats by increasing the functional connectivity between frontal association areas with retrosplenial and cingulate cortex. Furthermore, D-serine supplementation did not induce nephrotoxicity; instead, it restored the thickness of the epithelial tissue in the straight portion of proximal renal tubules of senescent rats suggesting that D-serine can reverse the detriment of aging-associated malfunction of peripheral tissue ( Rivera-Villaseñor et al, 2021 ). D-serine did not improve cognitive flexibility in young rats showing that D-serine effect is age-dependent pointing to a possible intervention in restoring the levels of D-serine to reverse cognitive functions that are affected in the aged brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms for this remain elusive. Rivera-Villasenor et al 296 further theorized that the expression of NMDA receptors on early osteoblasts decreases with increasing age, which may subsequently inhibit osteoblast maturation. The authors speculated that this would result in a secondary decrease in D-Ser release by mature osteoblasts, thereby promoting osteoclast maturation, bone resorption, and potentially progressing age-associated osteoporosis.…”
Section: Role Of D-aas In Eukaryotic Tissues and Their Role In Bone T...mentioning
confidence: 99%
“…302 D-Asp is also likely involved in aging of the skin and the development of arthrosclerosis, macular degeneration, and cataracts. 296,299,303 To this end, several D-AAs have been identified in human lenses in the eye, including D-Asp, D-Ser, D-Glu/Gln, and D-Phe, where the amount of racemization of D-Ser and D-Asp was significantly increased in cataract lenses when compared with age-matched healthy lenses. 304 In terms of cancer and tumor growth, D-AAs appear to display a varied response dependent on tumor etiology and condition.…”
Section: Role Of D-aas In Eukaryotic Tissues and Their Role In Bone T...mentioning
confidence: 99%
See 1 more Smart Citation
“…NMDARs have effects on multiple organs outside of the central nervous system [ 24 ]. Penile neuronal NOS, GluN1, and GluN2 NMDAR subunits are expressed in the cavernosal nerves of the corpus cavernosum and are frequently colocalized [ 25 , 26 ]. However, the role of NMDAR in corpus cavernosum is not well defined.…”
Section: Introductionmentioning
confidence: 99%